Reevaluating Associations between Prenatal Care Utilization and Current Trends in Preterm Birth - Champion, Macie L.; Bushman, Elisa T.; Martin, Kimberly D.; Battarbee, Ashley N.; Robbins, Lindsay S.; Andrews, William W.; Tita, Alan T. (American Journal of Perinatology, 2024)
Objective Studies have suggested an association between prenatal care (PNC) and preterm birth (PTB). We evaluated trends in PTB and association of PNC and PTB.Study Design This was a retrospective cohort study of singleton, viable nonanomalous deliveries from 1991 to 2018. PNC utilization was defined by World Health Organization using number of visits: adequate (≥8), suboptimal (5–7), and inadequate (<5). Primary outcome was PTB. Tests of trend were used to assess changes in PTB over time. Baseline characteristics and outcomes were compared. Logistic regression estimated the association of PNC and PTB. We evaluated for effect modification by year of birth.Results Of 92,294 patients, 14,057 (15%) had PTB. Inadequate and suboptimal PNC were associated with higher odds of PTB compared to adequate PNC (adjusted odds ratios = [aOR 6.21], 95% confidence interval [CI]: 5.84–6.60; aOR = 3.57, 95% CI: 3.36–3.79). Inadequate PNC was associated with higher odds of PTB over time (effect modification p < 0.0001). Inadequate PNC was associated with 5.4 times higher odds of PTB in 1998, 7.0 times in 2008, and 9.1 times in 2018.Conclusion Despite an increase in adequate PNC, there was a rise in PTB associated with inadequate and suboptimal PNC. PNC utilization was a stronger risk factor in recent years with higher PTB in patients who attended more than five PNC visits.Key Points
Keywords: preterm birth; prenatal care; prematurity; social determinants of health